906 Model school zone pilot project demonstrates results in improving pedestrian safety. (1st September 2016) - Gautam, Priti; Rosenthal, Kristin
Abstract : Background: From 2011–2014, the Model School Zone pilot project was implemented in 10 countries to improve pedestrian safety around 10 schools. Through multi-country data analysis, we sought to demonstrate that the program was effective in improving pedestrian safety and adaptable in low-, middle- and high-income countries. Methods: The project was implemented in three phases over an 18-month period. During Phase I, grantees selected a school based on specific criteria and conducted a baseline needs assessment. The needs assessment included a school zone infrastructure assessment tool, student knowledge and behaviour surveys, participatory research tools and parent surveys. In Phase II, grantees implemented interventions based on the needs and risks identified. Interventions focused on permanent infrastructure changes but also included education and advocacy initiatives. In Phase III, grantees evaluated the effectiveness of the interventions. Results: Behavioural surveys with 1, 606 children showed that most walk to and from school, most walk alone, and most do not feel safe near their schools. Parent surveys revealed that more than half felt uncomfortable about their child's safety on the way to school, with speed of cars the highest rated concern. Permanent modifications were made to environments around 10 schools in 10 countries, resulting in changed behaviour and reduced injury. In Vietnam, for example, the number of fatalities decreased three-fold. Results and lessons learned were used to develop the Safe School Zone project, launched in 2015. Conclusion: A phased approach to creating safe school zones focused on environmental changes, education and advocacy, is adaptable to low-, middle- and high- income countries, and leads to reduced fatalities and injuries.